Determinants Of Audit Quality With Integrated Reporting As A Moderator (Study On Financial Sector Companies In Indonesia And Malaysia) - Toduho, Dion M; Djaddang, Syahril; Lysandra, Shanti (SEAN Institute, 2024)
Many regulations require companies to be audited by qualified independent auditors. Financial statements of high quality will be more trusted by users of financial statements, such as investors, creditors, and governments. This study aims to analyze the factors that influence Audit Quality with Integrated Reporting as a moderating variable. The study was conducted on the Financial Sector in the Indonesia Stock Exchange and Malaysia, which are part of ASEAN, because the financial sector is involved in complex transactions and has a complex financial portfolio, so risk assessment and audit quality become more important.This study used binary logistic regression analysis with SPSS 23 software. The study analyzed 302 research units generated from 63 companies over 5 years of research (2018-2022). The results of the study showed that board independence had a positive effect on audit quality. Audit fees had a negative effect on audit quality. Audit reputation and board size had no effect on audit quality. Integrated reporting can moderate the effect of audit fees and board independence on audit quality. Integrated reporting cannot moderate the effect of board size on audit quality.